(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article studies the principles of sukuk - Islamic securities introduction, their economic efficiency and international experience. The main differences of sukuk from traditional bonds, as well as the possibilities of introducing sukuk securities in the conditions of Uzbekistan and their impact on the economy are analyzed. The article presents statistical data based on international practice and develops proposals